Collecting wild crop relatives in the northwestern steppes of Kazakhstan - Greene, S.L.=700 1 Hannan, R.; Afonin, A.; Dzyubenko, N.I.; Khusainov, A.
(En, Fr, Es)
ilus., 15 ref.
Keywords: ALLIUM; GERMOPLASMA; CONSERVACION DEL GERMOPLASMA; BIODIVERSIDAD; ITALIA; CEBOLLA